'Science is only half of it': Expert perspectives on operationalising infectious disease control cooperation in the ASEAN region - Anna Durrance-Bagale; Manar Marzouk; Aparna Ananthakrishnan; Michiko Nagashima-Hayashi; Sze Tung Lam; Manit Sittimart; Natasha Howard (Public Library of Science (PLoS), 2022)
Governmental awareness of the potential spread of infectious disease, exemplified by the current Covid-19 pandemic, ideally results in collective action, as countries coordinate a response that benefits all, contributing expertise, resources, knowledge and experience to achieve a common public good. However, operationalising regional cooperation is difficult, with barriers including lack of political will, regional heterogeneity, and existing geopolitical issues. We interviewed 23 people with regional expertise focusing on Asia, Africa, the Americas and Europe. All interviewees held senior positions in regional bodies or networks or had significant experience working with them. Operationalisation of a regional infectious disease body is complex but areas interviewees highlighted-organisational factors (e.g. integration and harmonisation; cross-border issues; funding, financing and sustainability; capacity-building; data sharing); governance and diplomacy (e.g. building collaborations and partnerships; communication; role of communities; diplomacy; leadership; ownership; sovereignty; political commitment); and stakeholders and multilateral agreements-will help promote successful operationalisation. The international infectious disease community has learned valuable lessons from the Covid-19 pandemic, not least the necessity of pooling human, financial and technological resources, constructing positive working relationships with neighbours, and sharing data. Without this kind of regional cooperation, infectious diseases will continue to threaten our future, and the next pandemic may have even more far-reaching effects.